Smart Monitoring System of Water Tank Based on Internet of Things - Husaini, Abdillah; Sary, Yoshida (Hanif Journal of Information Systems, 2024)
The first village located in Sei Meran Village, Pangkalan Susu Subdistrict, with a population of 640 people consisting of 325 men and 315 women. The village experienced clean water scarcity and received assistance in the form of a drilled well, water pump, and water tank from the Langkat Police Chief through the POLRI Cares for the Environment program. This program significantly improved villagers' access to clean water. However, the village administration and the village head found it challenging to monitor and calculate the fair distribution of clean water. This issue was addressed by implementing an Internet of Things (IoT)-based smart water tank system. This automated system incorporates various sensors, including an ultrasonic sensor and a relay module, to control the water pump and fill the water tank. Additionally, a 4x4 keypad allows villagers to enter an access code that activates the solenoid valve and water flow sensor to measure the distributed water volume. The system can be remotely monitored via the Blynk application using internet access. The ESP8266 microcontroller serves as the data center and control unit. The test results show that the ultrasonic sensor has an average accuracy of 98.7% in measuring distance, while the flow meter sensor has an average accuracy of 98.3% in measuring water flow volume. This system can accurately and efficiently monitor water levels and water withdrawal, automating the water resource management process in the tank.